2021
DOI: 10.1002/csc2.20407
|View full text |Cite
|
Sign up to set email alerts
|

Perennial ryegrass phytotoxicity increases with mesotrione rate and growth‐promoting environmental conditions

Abstract: Bleaching of young leaf tissue is a common response to the herbicide mesotrione and varies from one application to another. To better elucidate factors that may contribute to perennial ryegrass (Lolium perenne L.) phytotoxicity from mesotrione, studies were conducted at Blacksburg, VA. Continuous field monitoring of temperature, humidity, solar radiation, soil moisture, and leaf wetness was used to elucidate environmental conditions that led to perennial ryegrass injury by mesotrione applied at 0.14 kg a.i. ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…There was a large number of tillers in both experiments for perennial grass, which produces its highest number of tillers in early summer, while the number of tillers of annual bluegrass is considered to be highest in early autumn (Brede and Duich, 1986). As previously mentioned (McCurdy et al, 2008;Goncalves et al, 2020), it is important not to use Mes under conditions of rapid turfgrass growth, because injuries of perennial ryegrass could occur. It has been also confirmed (Kennedy, 2016) and in the present study, that Mes can act against annual bluegrass but has limited specificity.…”
Section: Discussionmentioning
confidence: 85%
“…There was a large number of tillers in both experiments for perennial grass, which produces its highest number of tillers in early summer, while the number of tillers of annual bluegrass is considered to be highest in early autumn (Brede and Duich, 1986). As previously mentioned (McCurdy et al, 2008;Goncalves et al, 2020), it is important not to use Mes under conditions of rapid turfgrass growth, because injuries of perennial ryegrass could occur. It has been also confirmed (Kennedy, 2016) and in the present study, that Mes can act against annual bluegrass but has limited specificity.…”
Section: Discussionmentioning
confidence: 85%
“…In turfgrass, mesotrione controlled crabgrass (Digitaria spp.) better when N was applied at $ 10 kg•ha À1 within 3 d of mesotrione application (Beck et al, 2015;Elmore at al., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Because of mesotrione's soil activity, its applications are less dependent on leaf moisture for absorption. Although mesotrione is not dependent on leaf moisture for absorption, relative humidity will influence and increase turfgrass injury (Goddard et al 2010;Gonçalves et al 2021). Goddard et al (2007) reported that dew presence at the time of application did not influence the control of dandelion or white clover by combination granules of mesotrione plus fertilizer in contrast to a dew-dependent granular product containing 2,4-D and MCPP.…”
Section: Introductionmentioning
confidence: 99%